한국인에서 오미데네팍 이소프로필 0.002% 점안액의 안전성 및 효용성 분석 - 이한상; 이상엽; 배형원; 김찬윤; 최웅락 (Daihan angwa haghoi jabji, 2023)
목적: 한국인 녹내장 환자에서 오미데네팍 이소프로필 0.002% 점안액의 안정성 및 효용성을 분석하고자 한다. 대상과 방법: 2021년 5월 1일부터 2022년 6월 30일까지 녹내장 또는 고안압으로 진단받고 오미데네팍 이소프로필 0.002% 점안 치료를 받은 환자들 306명을 대상으로 후향적 연구를 시행하였다. 치료 시작 후 1개월, 3개월 및 6개월 후의 안압 변화량 및 부작용의종류, 발생 빈도를 분석하였다. 결과: 최종적으로 선정 기준을 만족하여 연구에 포함된 환자는 235명이었다. 오미데네팍 이소프로필을 치료받은 전체 환자군에서, 평균 안압은 치료 전 16.5 ± 3.4 mmHg에서 1개월 후 14.5 ± 3.0 mmHg, 3개월 후 14.3 ± 2.7 mmHg, 6개월 후 14.7 ± 3.1 mmHg로감소하였으며, 치료 6개월 평균 안압 변화량은 -1.6 ± 2.8 mmHg (p<0.001)였다. 녹내장 유형별 분석 결과, 치료 6개월 평균 안압변화량은 정상안압녹내장, 개방우각녹내장, 고안압증에서 진단명에 관계없이 모두 유의미한 안압하강 효과를 보였다(p<0.05). 부작용발생 빈도는 전체 환자군의 29.8%에서 발생하였으며, 가장 흔한 부작용은 충혈(18.7%)이었다. 오미데네팍 이소프로필 점안 후 포도막염을 보인 사례는 1명(0.4%)에서 확인되었으며, 이외 전신적 부작용이 확인된 사례는 없었다. 결론: 오미데네팍 이소프로필은 한국인 녹내장 및 고안압 환자를 대상으로 다양한 유형에서 안압을 낮추는 효과를 보였다. 이는 녹내장 및 고안압 환자의 치료에 있어 잠재적 일차 치료제로 사용될 수 있음을 시사한다. Purpose: This study aimed to analyze the clinical efficacy and safety of omidenepag isopropyl (OMDI) 0.002% in Korean patients. Methods: A retrospective study was conducted involving 306 patients diagnosed with glaucoma or ocular hypertension, who were administered OMDI 0.002% from May 2021 to June 2022. The primary outcomes were the change in intraocular pressure (IOP) at months 1, 3, and 6 compared to the baseline IOP, and the reactions to the OMDI drug. Results: Out of 235 patients who met the study inclusion criteria, the mean IOP was 16.5 ± 3.4 mmHg at baseline, 14.5 ± 3.0 mmHg at month 1, 14.3 ± 2.7 mmHg at month 3, and 14.7 ± 3.1 mmHg at month 6. The mean IOP reduction at month 6 was -1.6 ± 2.8 mmHg (p < 0.001). On analyzing the IOP by types of glaucoma, the mean IOP change at the 6-month point showed statistically significant results in all types, including normal tension glaucoma, primary open-angle glaucoma, and ocular hypertension (p < 0.05). The frequency of side effects in all patients was 29.8%, with the most commonly reported adverse drug reaction being hyperemia in 18.7% of the total patients. There was one case (0.4%) of uveitis after OMDI administration, but no other systemic adverse drug reactions were reported. Conclusions: Omidenepag isopropyl demonstrated a statistically significant IOP-lowering effect in Korean patients with various types of glaucoma. This suggests that OMDI could potentially serve as a first-line treatment for glaucoma. KCI Citation Count: 0